Analytic Pricing of Employee Stock Options - Cvitanić, Jakša; Wiener, Zvi; Zapatero, Fernando (Review of Financial Studies, 2008)
[We introduce a model that captures the main properties that characterize employee stock options (ESO). We discuss the likelihood of early voluntary ESO exercise, and the obligation to exercise immediately if the employee leaves the firm, except if this happens before options are vested, in which case the options are forfeited. We derive an analytic formula for the price of the ESO and in a case study compare it to alternative methods.]